IMPROVING THE STUDENTS SPEAKING ABILITY THROUGH ROLE PLAY METHOD - Juvrianto CJ (IJET (Indonesian Journal of English Teaching), 2018)
This research highlights the speaking ability of the students which categorized in tenth year students of SMA Negeri 3 Parepare . The students were taught through role play method to know the improvement of the students speaking ability. The data collected in 2012 by applying quasi-experimental method, with two group pre-test and post-test design. The samples were taken of the research were consisted of 43 students from two classes taken from the population. The result of the data analysis shows that the students’ speaking mastery improved significantly. It was showed by the mean score of pre-test was 49.34 and the post-test was 71.304. It shows that the use of role play method can improve the students’ speaking ability of the tenth year students of SMA Negeri 3 Parepare significantly. Besides the different score of pre-test and post-test, the mean score of the students in post-test was 71.304 is higher than the Kriteria Ketuntasan Minimal (70) in SMA Negeri 3 Parepare. After analyzing the data by using the test formula, the result of t-test value in post-test was 1.868 and t-table value was 1.684. It means that the t-test value (1.868) was higher than t-table value (1.684). Those indicate that H1 was accepted and H0was rejected and the students who were taught through role play method are better than the students who were taught through conventional method.This research highlights the speaking ability of the students which categorized in tenth year students of SMA Negeri 3 Parepare . The students were taught through role play method to know the improvement of the students speaking ability. The data collected in 2012 by applying quasi-experimental method, with two group pre-test and post-test design. The samples were taken of the research were consisted of 43 students from two classes taken from the population. The result of the data analysis shows that the students’ speaking mastery improved significantly. It was showed by the mean score of pre-test was 49.34 and the post-test was 71.304. It shows that the use of role play method can improve the students’ speaking ability of the tenth year students of SMA Negeri 3 Parepare significantly. Besides the different score of pre-test and post-test, the mean score of the students in post-test was 71.304 is higher than the Kriteria Ketuntasan Minimal (70) in SMA Negeri 3 Parepare. After analyzing the data by using the test formula, the result of t-test value in post-test was 1.868 and t-table value was 1.684. It means that the t-test value (1.868) was higher than t-table value (1.684). Those indicate that H1 was accepted and H0 was rejected and the students who were taught through role play method are better than the students who were taught through conventional method.